The AI revolution in Accounting Practice : Threat or Opportunity for the Accounting Profession? - Fauzi Fauzi (Oikonomia : Journal of Management Economics and Accounting, 2026)
This study explores whether the rapid integration of Artificial Intelligence (AI) into accounting practice represents a threat or an opportunity for the accounting profession. AI technologies such as Robotic Process Automation, machine learning, and predictive analytics are transforming traditional accounting tasks by automating routine processes, enhancing audit procedures, and enabling real-time reporting and decision support. A qualitative descriptive approach was employed through a systematic literature review and semi structured interviews with accounting practitioners who actively use AI-based tools in their work. The findings indicate that AI significantly reduces repetitive manual work, improves accuracy, and enhances fraud detection and analytical capabilities. At the same time, AI creates challenges related to skill gaps, ethical concerns, and data governance. However, most practitioners perceive AI as a complementary tool that shifts accountants’ roles toward data analysis, strategic advisory, and AI governance rather than replacing them. The study concludes that AI represents a professional transformation opportunity, provided that accountants adapt through upskilling, ethical awareness, and technological competence. The future of the accounting profession depends not on resisting AI, but on integrating it to enhance value creation and decision-making capabilities.